Benthic foraminiferal biofacies and stable isotopic record of St. Stephens Quarry, Alabama - Kenneth G Miller; James V Browning; Marie-Pierre Aubry; Bridget S Wade; Miriam E Katz; Andrew A Kulpecz; James D Wright (PANGAEA, 2011)
We integrate upper Eocene-lower Oligocene lithostratigraphic, magnetostratigraphic, biostratigraphic, stable isotopic, benthic foraminiferal faunal, downhole log, and sequence stratigraphic studies from the Alabama St. Stephens Quarry (SSQ) core hole, linking global ice volume, sea level, and temperature changes through the greenhouse to icehouse transition of the Cenozoic. We show that the SSQ succession is dissected by hiatuses associated with sequence boundaries. Three previously reported sequence boundaries are well dated here: North Twistwood Creek-Cocoa (35.4-35.9 Ma), Mint Spring-Red Bluff (33.0 Ma), and Bucatunna-Chickasawhay (the mid-Oligocene fall, ca. 30.2 Ma). In addition, we document three previously undetected or controversial sequences: mid-Pachuta (33.9-35.0 Ma), Shubuta-Bumpnose (lowermost Oligocene, ca. 33.6 Ma), and Byram-Glendon (30.5-31.7 Ma). An ~0.9 per mil d18O increase in the SSQ core hole is correlated to the global earliest Oligocene (Oi1) event using magnetobiostratigraphy; this increase is associated with the Shubuta-Bumpnose contact, an erosional surface, and a biofacies shift in the core hole, providing a first-order correlation between ice growth and a sequence boundary that indicates a sea-level fall. The d18O increase is associated with a eustatic fall of ~55 m, indicating that ~0.4 per mil of the increase at Oi1 time was due to temperature. Maximum d18O values of Oi1 occur above the sequence boundary, requiring that deposition resumed during the lowest eustatic lowstand. A precursor d18O increase of 0.5 per mil (33.8 Ma, midchron C13r) at SSQ correlates with a 0.5 per mil increase in the deep Pacific Ocean; the lack of evidence for a sea-level change with the precursor suggests that this was primarily a cooling event, not an ice-volume event. Eocene-Oligocene shelf water temperatures of ~17-19 °C at SSQ are similar to modern values for 100 m water depth in this region. Our study establishes the relationships among ice volume, d18O, and sequences: a latest Eocene cooling event was followed by an earliest Oligocene ice volume and cooling event that lowered sea level and formed a sequence boundary during the early stages of eustatic fall.
Supplement to: Miller, KG et al. (2008): Eocene-Oligocene global climate and sea-level changes: St. Stephens Quarry, Alabama. Geological Society of America Bulletin, 120(1/2), 34-53, https://doi.org/10.1130/B26105.1